A Comparison of Learner Intent and Behaviour in Live and Archived MOOCs - Campbell, Jennifer; Gibbs, Alison; Najafi, Hedieh; Severinski, Cody (International Review of Research in Open and Distributed Learning, 2014)
The advent of massive open online courses (MOOCs) has created opportunities for learning that are clearly in high demand, but the direction in which MOOCs should evolve to best meet the interests and needs of learners is less apparent. Motivated by our interest in whether there are potential and purpose for archived MOOCs to be used as learning resources beyond and between instructor-led live-sessions, we examined the use of a statistics MOOC and a computer science MOOC, both of which were made available as archived-courses after a live-session and for which enrolment continued to grow while archived. Using data collected from surveys of learner demographics and intent, the course database of major learner activity, and the detailed clickstream of all learner actions, we compared the demographics, intent, and behaviour of live- and archived-learners. We found that archived-learners were interested in the live-MOOC and that their patterns of use of course materials, such as the number and sequence of videos they watched, the number of assessments they completed, their demonstration of self-regulatory behaviour, and their rate of participation in the discussion forums, were similar to the live-learners. In addition, we found evidence of learners drawing on an archived-MOOC for use as reference material. Anticipated areas of impact of this work include implications for the future development of MOOCs as resources for self-study and professional development, and in support of learner success in other courses.